LncRNA TUG1 reverses LPS-induced cell apoptosis and inflammation of macrophage via targeting MiR-221-3p/SPRED2 axis. Issue 12 (1st December 2020) - Hu, Lili; Ye, Hongwei; Liao, Jianjun
ABSTRACT: This study aimed to identify the role of lncRNA TUG1 with miR-221-3p on mice with lipopolysaccharide (LPS)-induced acute respiratory distress syndrome (ARDS). Animal model was established, and lung tissue histopathologic status and permeability were detected by hematoxylin-eosin (HE) or Evans blue dye assay respectively. Levels of inflammation cytokines, lncRNA TUG1, miR-221-3p, sprouty related EVH1 domain-containing 2 (SPRED2), and phosphorylated (p)-ERK1/2 were determined by ELISA, qRT-PCR or Western blot. Pulmonary impairment and apoptosis were examined by flow cytometry. We observed that LPS up-regulated levels of tumor necrosis factor-α (TNF-α), Interleukin-1β (1L-1β), and ERK1/2 phosphorylation, and reduced SPRED2 levels, which were rescued by overexpressed lncRNA TUG1. StarBase and dual-luciferase reporter assay verified that miR-221-3p was targeted by lncRNA TUG1. MiR-221-3p could reverse the effect of lncRNA TUG1 on cell apoptosis, levels of TNF-α, IL-1β, SPRED2, and p-ERK1/2. Therefore, overexpressed lncRNA TUG1 attenuated LPS-induced pulmonary impairment in ARDS mice via regulating miR-221-3p/SPRED2 axis. GRAPHICAL ABSTRACT: uf0001 Overexpressed TUG1 could alleviate LPS-induced up-regulation of miR-221-3p expression and RAW 264.7 macrophage apoptosis and inflammatory cytokine accumulation, which was reversed by overexpressed miR-221-3p.